Mimicking reproductive endocrinology to achieve successful pregnancy in frozen embryo replacement cycle in luteinized unruptured follicle (LUF) - Jain, Namita; Malik, Sonia; Prakash, Ved (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Frozen embryo replacement cycles are commonly performed in all ART centres for various indications. In FER cycles, aim is to achieve the synchronization between the endometrium and the embryo. It can be undertaken in a natural or in an artificially prepared endometrium. Artificial preparation utilizes either the ovulation induction agents or hormones. Luteinized unruptured follicle is commonly encountered nowadays due to better resonance USG machines and frequent monitoring. It is still unclear among the practitioners whether to perform an embryo transfer in LUF. In this case report, authors are highlighting that in case of FER cycles using ovulation induction agent, despite inability to ovulate (LUF), if authors are able to achieve optimum synchronization between endometrium and the embryo using USG and serum hormonal levels, successful outcome could be expected.